Wiatr od Morza . no. 4, 1981 - "Solidarność" Sekcja Oświaty i Wychowania, [ed. Andrzej Hojan, graphic design Katarzyna Dobrowolska] ([s.n.], 1981)
Creation and circulation: For trade-union use; After introduction of the Martial Law publication suspended. Republished in 1988